Step-by-step explanation:
error
Polynomial error: You have used illegal character ( = )..
Step by Step Solution
More Icon
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
49-((2+5)*2)=0
STEP
1
:
Equations which are never true:
1.1 Solve : 35 = 0
This equation has no solution.
A a non-zero constant never equals zero.
No solutions found
Answer:
t=0
Step-by-step explanation:
First, we expand everything. The left-hand side is -3(2t) - 1(-3), and we expand it to be -6t+3. The right-hand side is t+t+t+3, and we can reduce it to 3t+3. Now that we have both sides of the equation, we set them to each other.
-6t+3=3t+3 (subtract 3 on both sides)
-6t=3t (add 6t to both sides)
9t =0 (divide by 9)
t=0
Adding what rational expressions?
Hello,
Let's r the ration
We suppose x ≠0
x=r*(x-2)==>r=x/(x-2)
x+3=r*x==> (x+3)/x=x/(x-2)==>(x+3)(x-2)=x²
==>x²+3x-2x-6=x² ==>x-6=0==>x=6
x-2=6-4=4
x=6
x+3=6+3=9
6=4*3/2
9=6*3/2
Ration 3/2
First term: 4